Non-Limiting Technology: An Initial Proposal of an Emerging Concept in Software Engineering - Tatiana Cartagena; Rafael Ara´ujo Rodrigues (Anais do Encontro Anual de Tecnologia da Informação, 2025)
This paper presents the initial proposal of Non-Limiting Technology (NLT), an emerging concept in Software Engineering that seeks to rethink the role of technology in human development. Unlike paradigms such as accessibility, usability, and inclusive design, NLT is based on the principle that technology should not impose limits on individuals’ cognitive, social, or ethical capacities, but rather enhance their growth. The paper discusses related theoretical foundations, defines the initial conceptual pillars of NLT, and points out future research directions. It represents a conceptual effort to invite the community to explore new metrics and practices for a more human-centered software engineering.